2022
DOI: 10.1088/1538-3873/ac495a
|View full text |Cite
|
Sign up to set email alerts
|

Transit Timing Variation of XO-3b: Evidence for Tidal Evolution of Hot Jupiter with High Eccentricity

Abstract: Observed transit timing variation (TTV) potentially reveals the period decay caused by star-planet tidal interaction which can explain the orbital migration of hot Jupiters. We report the TTV of XO-3b, using TESS observed timings and archival timings. We generate a photometric pipeline to produce light curves from raw TESS images and find the difference between our pipeline and TESS PDC is negligible for timing analysis. TESS timing presents a shift of 17.6 minutes (80σ), earlier than the prediction from the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…A recent analysis of TESS data confirmed this decay rate, reducing the error bars below 1 ms yr −1 (Wong et al 2022). Possible tidal decay has also been reported for several other systems, including XO-3 b (Ivshina & Winn 2022;Yang & Wei 2022), WASP-19 b (Patra et al 2020;Ivshina & Winn 2022), TrES-1 b, TrES-2 b, HAT-P-19 b (Hagey et al 2022), Kepler-1658b (Vissapragada et al 2022, and KELT-9 b (Harre et al 2023). However, definitive confirmation will likely require additional years of observations, and knowing which planets to prioritize requires understanding how decay is detected and what parameters best suit a system to exhibit detectable decay.…”
Section: Introductionsupporting
confidence: 70%
“…A recent analysis of TESS data confirmed this decay rate, reducing the error bars below 1 ms yr −1 (Wong et al 2022). Possible tidal decay has also been reported for several other systems, including XO-3 b (Ivshina & Winn 2022;Yang & Wei 2022), WASP-19 b (Patra et al 2020;Ivshina & Winn 2022), TrES-1 b, TrES-2 b, HAT-P-19 b (Hagey et al 2022), Kepler-1658b (Vissapragada et al 2022, and KELT-9 b (Harre et al 2023). However, definitive confirmation will likely require additional years of observations, and knowing which planets to prioritize requires understanding how decay is detected and what parameters best suit a system to exhibit detectable decay.…”
Section: Introductionsupporting
confidence: 70%
“…XO-3 b and WASP-17 b are the only two systems on both of our interested candidate lists. For XO-3 b, as we have already pointed out in Section 4.1.15, the earlier work of Yang & Wei (2022) reported a rate of decay of −195 ± 9 ms yr −1 , whereas in this work we have obtained a much smaller value of −32 ± 5 ms yr −1 with additional TESS data. For WASP-17 b, Shan et al (2023) found it shows the largest late offset timing of 70.8 ± 11.7 minutes using a linear ephemeris model, while we find it to be consistent with =  P 0 ms yr −1 after the removal of one single transit-time data with a very small error bar (∼8 s).…”
Section: Comparison To Thesupporting
confidence: 49%
“…It orbits an F5V star with an orbital period of 3.192 days, with an eccentric and misaligned orbit (Hébrard et al 2008). TESS transit-timing analysis of this system was performed by Yang & Wei (2022), who found dP/dE = − 6.2 × 10 −9 ± 2.9 × 10 −10 , which is equivalent to = -  P 195 9 ms yr −1 . A subsequent study by Ivshina & Winn (2022) found a rate of decay of −182.08 ± 12.96 ms yr −1 .…”
Section: Tres-1 Bmentioning
confidence: 99%
“…In the past few years, as observational baselines have passed the decade mark for many systems, a growing number of UHJs around main-sequence stars have been presented with suggestions that they may have decreasing orbital periods. These include HAT-P-19 b (Hagey et al 2022) Maciejewski et al 2021;Hagey et al 2022;Ivshina & Winn 2022;Yeh et al 2024); WASP-4 b (Bouma et al 2020;Hagey et al 2022;Harre et al 2023); WASP-19 b (Patra et al 2020;Ivshina & Winn 2022); WASP-32 b (but not significant; Sun et al 2023); WASP-43 b as reported by Sun et al (2018), though not by Hagey et al (2022); and XO-3 b (Ivshina & Winn 2022;Yang & Wei 2022). Many of these claimed detections are acknowledged in the original publications to be of marginal significance, however.…”
Section: Introductionmentioning
confidence: 91%